Role of calcium-activated potassium channels in the heart - William T Clusin (Cardiology Plus, 2017)
Ability of intracellular calcium to open K+-selective channels in an excitable membrane and to hasten repolarization of an action potential or inhibit firing is a fundamental principle of biology first recognized in the mid-1970s. There are several types of these channels, the principal ones being large conductance (BK) and small conductance (SK). While these channels are clearly more prevalent in the brain and other neuronal tissue, they are definitely present in various parts of the heart and the information about their role has gradually emerged over the past 40 years. The structure and function of these channels are described in the first part of this review. SK channels are opened exclusively by [Ca2+]i, while BK channels are sensitive to both voltage and [Ca2+]i. Opening of calcium-activated potassium channels does not seem to be the primary mechanism of action potential repolarization in the heart as once thought, and further research is needed to clarify if shortening of the action potential during acute myocardial infarction is due to opening of these channels due to “calcium overload.” Some evidence for a role of SK channels in ischemia-induced action potential shortening has been obtained. Calcium-activated K+ channels in the ventricular myocardium are upregulated in heart failure which may have an antiarrhythmic effect by counteracting calcium-dependent inward currents. BK channels have been implicated in ischemic preconditioning. Mutations affecting BK and SK channels do not seem to be an important cause of long QT syndrome, but genome-wide association studies that focus on these channels should be performed in patients or families with long QT or genetically mediated sudden death.